Depth-related gradients in community structure and relatedness of bivalves and isopods in the Southern Ocean. (May 2016) - Brandt, Angelika; Linse, Katrin; Ellingsen, Kari E.; Somerfield, Paul J.
Highlights: Species richness of isopods varied with depth, richness of bivalves did not. Different shallow and deep communities overlap from 2000 to 4000 m. There is no evidence of a specialized slope fauna of either isopods or bivalves. Most species are rare, but each has closely-related species in the same depth range. Abstract: Despite increased research over the last decade, diversity patterns in Antarctic deep-sea benthic taxa and their driving forces are only marginally known. Depth-related patterns of diversity and distribution of isopods and bivalves collected in the Atlantic sector of the Southern Ocean are analysed. The data, sampled by epibenthic sledge at 40 deep-sea stations from the upper continental slope to the hadal zone (774–6348 m) over a wide area of the Southern Ocean, comprises 619 species of isopods and 81 species of bivalves. There were more species of isopods than bivalves in all samples, and species per station varied from 2 to 85 for isopods and from 0 to 18 for bivalves. Most species were rare, with 72% of isopod species restricted to one or two stations, and 45% of bivalves. Among less-rare species bivalves tended to have wider distributions than isopods. The species richness of isopods varied with depth, showing a weak unimodal curve with a peak at 2000–4000 m, while the richness of bivalves did not. Multivariate analyses indicate that there are two main assemblages in the Southern Ocean, one shallow and one deep. These overlap over a large depth-range (2000–4000 m). Comparing analyses based on the Sørensen resemblance measure and Γ + (incorporating relatedness among species) indicates that rare species tend to have other closely related species within the same depth band. Analysis of relatedness among species indicates that the taxonomic variety of bivalves tends to decline at depth, whereas that of isopods is maintained. This, it is speculated, may indicate that the available energy at depth is insufficient to maintain a range of bivalve life-history strategies.